Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction